Awareness and Recall of Alcohol Advertising through Similar Brands to Alcoholic Beverages - วงษ์สิริโสภาคย์ สิริกุล (Journal of Health Science of Thailand, 2022)
Statistical survey of the National Statistical Office in 2017 found that 28.4% of Thai people aged between 15 years and over consumed alcohol: 47.5% among male and 10.6% among female, which indicates that the alcoholic beverage business has a huge market value and becomes a very competitive trade. Although the Alcohol Control Act B.E. 2551 (2008) is a control tool, there are modifications of the advertisement to promote alcohol sale without being punished by the law. The objectives of this research was to assess the differences between male and female perception and motivation to buy alcoholic beverages based on the advertisements using the logos or symbols similar to those of alcohol products. The samples were 3,267 persons aged 15-60 years living in different regions of Thailand. Data were collected by using questionnaires, and were analyzed by the use of frequency, percentage, mean, and Chiหquare. It was found that 50.2% of the participants were females, with an average age of 34 years, and 78.1% of them had seen alcohol advertisement on television. It was observed that the samples were able to aware and recall the brands of alcoholic beverages, even though the advertisements were for non- alcohol products; and there was difference oerception between sex in some advertisements. Therefore, there is a need to revise the law on alcohol to control the advrtisememts that mimic alcohol products in order to reduce people’s perception and mitivation to purchase alcohol, especially among women, children, and the youth.